(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Patients of stenosing tenosynovitis or trigger finger presents with pain, swelling, limitation of finger movement, and triggering. Thickening of the A1 pulley, with resultant entrapment of flexor tendons, is the primary pathology. In failed conservative treatment, surgical release by open or percutaneous technique is used. The aim of this study was to evaluate the results of percutaneous release of trigger fingers using hypodermic 18-gauge needle under local anesthesia. Methods: A cross sectional study of percutaneous release of trigger fingers using hypodermic 18-gauge needle under local anesthesia was performed in outpatient clinic at Janaki Medical College Teaching Hospital, Janakpur, Nepal, from July 2016 to September 2017. Informed consent was obtained. All the patients were followed up on 3rd day, 1st week and one month in outpatient department, and further telephone follow up at three and six months after surgery. Results: There were 38 patients, female 25 and male 13, age 24 to 67 years. Successful release was achieved in 36/38 (95%) with normal activities within 48 hours. None had complications like digital neurovascular injury or tendon bowstringing. One patient had superficial skin infection and was treated successfully with oral antibiotics. Two (5.2%) had pain and recurrent triggering requiring open release in the first week. At one, three and six months follow up patients reported no triggering of released fingers. Conclusions: Percutaneous release with hypodermic 18-gauge needle under local anesthesia in the treatment of trigger finger was an effective and convenient method with a low complication rate.